Heinemüller's Conception of Political Ideas in The Hamlet Machine - Inheritance and Comparison with Brecht - Chen, Kexu (International Journal of Social Sciences and Public Administration, 2024)
Heinemüller's original intention in creating The Hamlet Machine was to use Hamlet as a vehicle for political allusion to the socialist world of the late Cold War. He tried to create a variant of the Hamlet theme in a Communist country after Stalin’s death…Combined with the creator's own political leanings, it is clear that the seemingly chaotic plot logic of the work is wrapped up in the political metaphorical imagery of the violence and darkness characteristic of a brutal play, which is a reflection of both the external pioneering nature of the work and its internal political nature. In addition, the frequent traces of interstitial effects in the staging of this work, combined with some echoes of Heiner Müller's view of Brecht's political theatre, thus confirm Heiner Müller's critical inheritance of Brecht's plays.